Pendampingan Usaha Menengah Kecil Masyarakat Melalui Digital Marketing untuk Menunjang Pemasaran Produk - Fauziah, Muna; A'za, Tika Zamrotul; Hilmiyah, Syarifatul; Latifah, Laillatul; Syihab, Ikfina Farhani (Yayasan Keluarga Guru Mandiri, 2022)
Digital marketing is a way to market products for business actors through online media by maximizing the various available marketplaces so that the product marketing process can take place optimally. Technological developments help empower people to be able to compete globally. Giripurno Village is located in Karanganyar District, Kebumen Regency, and Central Java with high potential for human resources to expand the products of small and medium enterprises. The phenomenon of the Covid-19 pandemic has resulted in a decrease in the income of small and medium-sized businesses and the cessation of local activities. From the discovery of these assets, community service activities aim to assist small and medium-sized businesses in the community through digital marketing to support product marketing. The method applied is Asset Based Community Development. The target is the owners of small and medium enterprises as many as 28 people. The results of this community service help small and medium businesses of the Desar Giripurno community in understanding the concept of digital marketing, creating online shop accounts (Facebook, Instagram, and Shope), promoting/marketing their products through the marketplace, as well as the satisfaction of reflection results of 77.67% to activities community service-based assistance.